Antilithic Effects of Extracts from Urtica dentata Hand on Calcium Oxalate Urinary Stones in Rats - 向明 张莎莎 鲁憬莉 李璐璐 侯文睿 谢明星 曾莹 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
This study examined the potential antilithic effects of a traditional Chinese medicine Urtica dentata Hand （UDH） in experimental rats and screened the optimal extract of UDH as a possible therapeutic agent for kidney stones. The rat model of urinary calcium oxalate stones was induced by intragastric （i.g.） administration of 2 mL of 1.25% ethylene glycol （EG） and 1% ammonium chloride （AC） for 28 days and was confirmed by Color Doppler ultrasound imaging. The rats in different experimental groups were then intragastrically given petroleum ether extract （PEE）, N-butanol extract （NBE）, aqueous extract （AqE） of UDH, Jieshitong （positive control drug）, and saline, respectively. Treatment with NBE significantly reduced the elevated levels of urinary calcium, uric acid, phosphate, as well as increased urinary output. Accordingly, the increased calcium, oxalate levels and the number of calcium oxalate crystals deposits were remarkably reverted in the renal tissue of NBE-treated rats. In addition, NBE also prevented the impairment of renal function to decrease the contents of blood urea nitrogen （BUN） and creatinine. Taken together, these data suggest that NBE of UDH has a beneficial effect on calcium oxalate urinary stones in rats by flushing the stones out and protecting renal function.